1.57 Prolactin is locally produced in the synovium of patients with inflammatory arthritic diseases and promotes macrophage activation. (31st January 2014) - Tang, M W; Reedquist, K A; Garcia, S; Gerlag, D M; Tak, P P
Abstract : Background and Objectives: The sex hormone prolactin (PRL) has immunomodulatory properties, can be produced by immune cells, and elevated PRL serum levels have been reported in rheumatoid arthritis (RA) patients. Here we examined synovial expression of PRL and PRL receptor (PRLR) in patients with inflammatory arthritis, their expression in polarised macrophages from patients and healthy donors, and the effects of PRL on macrophage activation. Materials and Methods: PRL levels in paired synovial fluid (SF) and peripheral blood of RA (n = 19), psoriatic arthritis (PsA, n = 13) and gout (n = 11) patients were measured using an immunofluorescent metric assay. PRL mRNA expression was measured in synovial tissue (ST) of RA (n = 25), PsA (n = 11) and gout (n = 12) patients, and in macrophages differentiated in RA, PsA, spondyloarthritis (SpA) and gout SF by qPCR. PRLR protein expression was determined in ST of RA (n = 19), PsA (n = 15) and osteoarthritis (OA, n = 9) patients by immunohistochemistry and detected in specific cell types by immunofluorescence. IL-6 production by IFN-y and IL-10 -differentiated macrophages following stimulation with CD40L or TNF in the absence or presence of PRL was measured by ELISA. Results: PRL protein levels were similar in serum and SF of RA, PsA and gout patients, as was mRNA expression in RA, PsA and gout ST. Of interest, PRL mRNA expression significantly correlated with clinical disease parameters in PsA (DAS28, R = 0.729, P = 0.017) and RA (ESR, R = 0.424, P = 0.049). PRL expression was also detected in monocyte-derived macrophages from RA patients, and significantly higher ( P ≤0.01) in healthy donor macrophages differentiated in pooled SF of RA and PsA compared to SpA and gout SF. In RA SF-differentiated macrophages PRL production was increased by CD40L or IgG stimulation but not LPS or TNFα. Median (IQR) PRLR expression was significantly higher ( P <0.05) in RA [0.06 (0.00-0.33)] and PsA [0.18 (0.00-1.67)] ST compared to OA [0.00 (0.00-0.02)], and there was no significant difference in PRLR expression between (pre/postmenopausal) females and males, independently of disease. PRLR expression was mainly colocalised with CD68 + macrophages and vWF + endothelial cells. In vitro, PRLR was prominently expressed in IFN-y and IL-10 polarised monocyte-derived macrophages compared to macrophages polarised in GM-CSF, M-CSF or RA SF. In these macrophages, PRL stimulation significantly enhanced IL-6 production in response to TNFα or CD40L. Conclusions: Our results provide the first evidence that PRL is produced locally in the synovium of patients with inflammatory arthritis, and contributes to the activation of macrophages in the presence of other inflammatory stimuli.